Analisis Kualitas Instrumen Untuk Mengukur Kreatifitas Siswa Melalui Pembelajaran Berdiferensiasi - Umi Isrotun; Sumarno Sumarno; Muhtarom Muhtarom (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
Instruments are tools that researchers use to collect and measure quantitative information about the variables studied. As a tool for collecting research data, the quality of the instrument determines the quality of the data collected. In compiling an instrument to be used in research, it is necessary to pay attention to several things including the problems and variables to be studied, data sources, information in the instrument, types of data, easy and practical. Differentiated learning is learning that is expected to be able to coordinate student learning needs so it is hoped that through differentiated learning can provide students with broad opportunities so as to increase their activity. Creativity indicators include 1) Critical thinking, 2) High emotional sensitivity, 3) Talented, 4) High imagination. From the instrument in the form of an observation sheet that has been made consisting of sixteen items after the Aiken's test (1985) it can be said to be valid as a guide for researchers in observing student creativity in differentiated learning